Protocolized eye care prevents corneal complications in ventilated patients in a medical intensive care unit - Mohammad Feroz Azfar; Muhammad Faisal Khan; Abdulaziz H Alzeer (Saudi Journal of Anaesthesia, 2013)
Background: Eye care is an essential component in the management of critically ill patients. Standardized eye care can prevent corneal complications in ventilated patients. Objective: This study was designed to compare old and new practices of corneal care for reduction in corneal complications in ventilated patients. Methods: This study was done in three phases each of six month duration. Phase 1 was the ongoing practice of eye care in the unit. Before the start of phase 2, a new protocol was made for eye care. Corneal complications were observed in terms of haziness, dryness, and ulceration. All nursing staffs were educated and made compliant with the new protocol. In phase 2, a follow-up audit was done to check the effectiveness and compliance to protocol. In phase 3, a follow-up audit was started 3 months after phase 2. Results: In phase 1, total ventilated patients were 40 with 240 ventilator days. The corneal dryness rate was 40 per 1000 ventilator days while the haziness and ulceration rate was 16 per 1000 ventilator days each. In the second phase 2, total ventilated patients were 53 making 561 ventilator days. The rate of corneal haziness and dryness was 3.52 and 1.78 per 1000 ventilator days, respectively, with no case of corneal ulceration. In phase 3, the number of ventilated patients was 91 with 1114 ventilator days. The corneal dryness rate was 2.69 while the haziness and ulceration rate was 1.79 each. Conclusion: Protocolized eye care can reduce the risk of corneal complications in ventilated patients.